ANALISIS KESALAHAN BERBAHASA DALAM RUBRIK â€œFOKUSâ€ MAJALAH PENDAPA TAMANSISWA - Yosephus Dominikus Fernandez; Mukhlish Mukhlish (CARAKA, 2018)
This research aims to describe linguistics error on â€œFokusâ€ rubric of Pendapa Tamansiswa magazine. The errors identified are 1) spelling errors, 2) morphologic errors 3) syntactic errors 4) and lexicon errors. This is a qualitative descriptive research which focuses on sentences containing linguistics errors. The data are gathered from sixteen packs of rubric â€œFokusâ€ in Pendapa Tamansiswa magazine in eight bundle of publishing by using free intensive reading and noteÂ  taking techniques. The data were analyzed by using evenly distributed methods with direct-substance-distribution techniques, substituting techniques, disappearing techniques, extension techniques, and reversing techniques. The result showed that (1) there are 133 error sentences or 11,24% contain of error in letter using, dictions, punctuation, and spelling. (2) There are 8 sentences with morphologic errors or 0,68% which contain affixes and reduplications errors. (3) There are 70 syntactic errors in 70 sentences or 5,91% which contain sentence patterns errors and word choise of "tugas". (4) There are 50 sentences with lexicon errors or 4,23% which contain unappropriate choice of dictions, unsuitable choice of dictions, and "redundan" formating. (5) There are 161 sentences with mixed errors or 13,60% which consist (a) spelling and morphologic errors, (b) spelling and syntactic errors, (c) spelling and lexicon errors (d) morphologic and syntactic errors, (e) morphologic and lexicon errors, (f) syntactic and lexicon errors, (g) spelling, morphologic and syntactic errors, (h) spelling, syntactic, and lexicon errors, (i) morphologic, syntactic and lexicon errors, and (j) spelling, morphologic, syntactic, and lexicon errors.